2021
DOI: 10.3389/fmolb.2021.767856
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Cancer Landscape of HOX-Related lncRNAs and Their Association With Prognosis and Tumor Microenvironment

Abstract: The highly conserved homology cassette family (HOX) as well as 18 referenced long non-coding antisense transcripts (HOXATs) play vital roles in the development of some cancers. Nevertheless, their expression patterns as well as their association with cancer prognosis and the tumor microenvironment (TME) in pan-cancers are still unclear. Here, based on public databases, the expression levels of HOXATs, their prognostic potentials, and correlation with tumor mutation burden (TMB), immune cell infiltration, immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…33,34 Cells in this cluster also expressed MEIS1 , which is expressed by differentiating granule cells 35 and HOXB-AS1 , which is a member of a large family of non-coding transcripts that are abnormally expressed in a wide range of cancers. 36 Consistent with the expression of MEIS1 , gene set enrichment analysis suggested this cluster contained mature cells (Supplementary Fig. S3G, H).…”
Section: Resultssupporting
confidence: 56%
“…33,34 Cells in this cluster also expressed MEIS1 , which is expressed by differentiating granule cells 35 and HOXB-AS1 , which is a member of a large family of non-coding transcripts that are abnormally expressed in a wide range of cancers. 36 Consistent with the expression of MEIS1 , gene set enrichment analysis suggested this cluster contained mature cells (Supplementary Fig. S3G, H).…”
Section: Resultssupporting
confidence: 56%
“…The prognostic signature we constructed contains four lncRNAs, ANKRD10-IT1, HOXB-AS1, LINC00520 and LINC01165.One of these tumor types is HOXB-AS1, a cancer stimulator that has been linked to prognosis in various types of tumors [ 30 ]. A recent study has shown that HOXB-AS1 plays a part in pathways related to cancer and the immune system, indicating its potential involvement in the development of cancer and immune regulation in various types of cancer [ 31 ]. Furthermore, a notable association is observed between HOXB-AS1 and the immune scores in DLBCL, indicating a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the role of HOX genes on immunity or in the tumor microenvironment are limited. A previous study showed that HOX antisense transcript expression correlates with genes related to immune cell in ltration, speci c immune subtypes, and immune responses to cancer [15]. In colorectal cancer, high HOXC 6 expression is signi cantly associated with activation of cytokine pathways, expression of T cell attraction chemokines, in ltration of immune cells, and expression of immune checkpoint markers [16].…”
Section: Introductionmentioning
confidence: 99%